![\huge\red{heya!!!} \huge\red{heya!!!}](https://tex.z-dn.net/?f=%5Chuge%5Cred%7Bheya%21%21%21%7D)
...PLEASE GIVE THE VALUE...
❎❎DON'T SPAM❎❎
![](https://hi-static.z-dn.net/files/da7/cfda8340db1207a2eba23884dc020810.jpg)
Answers
Solution:
Given, 2/√(10 + 2√21) - 1/√(12 - 2√35) + 1/√(8 - 2√15)
= 2/√(7 + 3 + 2√21) - 1/√(7 + 5 - 2√35) + 1/√(5 + 3 - 2√15)
= 2/√{(√7)2 + (√3)2 + 2 *√7 * √3)} - 1/√{(√7)2 + (√5)2 - 2 *√7 * √3)} + 1/{(√5)2 + (√3)2 - 2 *√7 * √3)}
= 2/√(√7 + √3)2 - 1/√{(√7 - √5)2 + 1/√{(√5 - √3)2
= 2/(√7 + √3) - 1/(√7 - √5) + 1/(√5 - √3)
= {2 * (√7 - √3)}/{(√7 + √3)*(√7 - √3)} - {1 * (√7 + √5)}/{(√7 - √5)*(√7 + √5)} + {1 * (√5 + √3)}/{(√5 - √3)*(√5 + √3)}
= {2 * (√7 - √3)}/{(√7)2 - (√3)2 } - {1 * (√7 + √5)}/{(√7)2 - (√5)2 } + {1 * (√5 + √3)}/{(√5)2 - (√3)2 }
= {2 * (√7 - √3)}/(7 - 3) - (√7 + √5)/(7 - 5) + (√5 + √3)/(5 - 3)
= {2 * (√7 - √3)}/4 - (√7 + √5)/2 + (√5 + √3)/2
{2 * (√7 - √3)} - 2(√7 + √5) + 2(√5 + √3)/4
= {2√7 - 2√3 - 2√7 - 2√5 + 2√5 + 2√3}/4
= 0/4
= 0
So, the value of 2/√(10 + 2√21) - 1/√(12 - 2√35) + 1/√(8 - 2√15) is 0